2004
DOI: 10.1242/jeb.00765
|View full text |Cite
|
Sign up to set email alerts
|

Water calcium concentration modifies whole-body calcium uptake in sea bream larvae during short-term adaptation to altered salinities

Abstract: Whole-body calcium uptake was studied in gilthead sea bream larvae (9-83·mg) in response to changing environmental salinity and [Ca 2+ ]. Calcium uptake increased with increased fish size and salinity. Fish exposed to calcium-enriched, diluted seawater showed increased calcium uptake compared with fish in diluted seawater alone. Calcium uptake was unchanged in Na + -enriched, diluted seawater. Overall, [Ca 2+ ], and not salinity/osmolarity per se, appears to be the main factor contributing to calcium uptake. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Once in the cell, Ca 2+ is bound to proteins and actively pumped across the basolateral membrane into the blood by Ca 2+ -specific ATPases or exchanged for Na + in Na + /Ca 2+ exchangers facilitated by the Na + gradient created by Na + ,K + -ATPase (Hwang and Lee, 2007). In the GIT, Ca 2+ uptake occurs following dietary ingestion (Bucking and Wood, 2007) and drinking (Flik et al, 1995;Guerreiro et al, 2004). Drinking may play a larger role in marine fishes, whereby the drinking of seawater offsets dehydrative water loss, and is also a potential source of Ca environments, GIT Ca 2+ uptake may be minimized through reduced transcellular transport and increased excretion via paracellular pathways (Schoenmakers et al, 1993), and luminal Ca 2+ obtained through drinking is largely precipitated by the bicarbonate base (Wilson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Once in the cell, Ca 2+ is bound to proteins and actively pumped across the basolateral membrane into the blood by Ca 2+ -specific ATPases or exchanged for Na + in Na + /Ca 2+ exchangers facilitated by the Na + gradient created by Na + ,K + -ATPase (Hwang and Lee, 2007). In the GIT, Ca 2+ uptake occurs following dietary ingestion (Bucking and Wood, 2007) and drinking (Flik et al, 1995;Guerreiro et al, 2004). Drinking may play a larger role in marine fishes, whereby the drinking of seawater offsets dehydrative water loss, and is also a potential source of Ca environments, GIT Ca 2+ uptake may be minimized through reduced transcellular transport and increased excretion via paracellular pathways (Schoenmakers et al, 1993), and luminal Ca 2+ obtained through drinking is largely precipitated by the bicarbonate base (Wilson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Pthrp's role in bony fish has been studied, (11,32,33) and it may be a hypercalcemic factor, particularly in the gills. (34) The role of Pthrp in elephant shark remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…(10) Attempts to elucidate the normal role of Pthrp in bony fish indicated that it is probably a hypercalcemic factor (11,12) that has potential paracrine actions in skin and muscle. (10) This reflects its roles in bony-jawed vertebrates and indicates that functions have been conserved from fish to mammals.…”
Section: J Jbmrmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to regulation of the amount of water ingested by endocrine and environmental factors (Fuentes et al, 1996;Fuentes and Eddy, 1997a;Fuentes and Eddy, 1997b;Guerreiro et al, 2004;Guerreiro et al, 2001), the processing of imbibed fluid has a major impact in fish ion regulation. Ingested water is first processed in the oesophagus, where it undergoes selective absorption of NaCl (Hirano and Mayer-Gostan, 1976;Parmelee and Renfro, 1983), which lowers fluid osmolality and is believed to enhance water absorption in the intestine.…”
mentioning
confidence: 99%